2018
DOI: 10.1080/09593330.2018.1496148
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the most suitable microalgae species to treat the effluent from an anaerobic membrane bioreactor

Abstract: Conventional treatments for nutrient removal in wastewater are shifting to Anaerobic Membrane Bioreactors, which produce a high-quality effluent with minimum sludge production. The effluent resulting contains high nitrogen and phosphorus load that can be eliminated by microalgae culture. The aim of this study is to evaluate the ammonium and phosphorus removal rate of different microalgae species in the effluent of an anaerobic treatment. For that, 4 different microalgae species have been tested (Chlamydomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…When the system is nutrient-limited, 24 N t , NH 4 and P can also have a significant effect in MPBR performance. In this respect, other authors have reported microalgae limitation when ammonium and phosphorus are under 10 and 1 mg•L -1 , respectively(Pachés et al, 2018). Since these effluent variables are also related to microalgae nutrient uptake, it is therefore reasonable to expect that P, NH 4 and N t presented a relatively high inverse correlation with microalgae performance(Figure 6a).…”
mentioning
confidence: 73%
“…When the system is nutrient-limited, 24 N t , NH 4 and P can also have a significant effect in MPBR performance. In this respect, other authors have reported microalgae limitation when ammonium and phosphorus are under 10 and 1 mg•L -1 , respectively(Pachés et al, 2018). Since these effluent variables are also related to microalgae nutrient uptake, it is therefore reasonable to expect that P, NH 4 and N t presented a relatively high inverse correlation with microalgae performance(Figure 6a).…”
mentioning
confidence: 73%
“…However, at this time, the non-nitrification-inhibited PBR had nitrogen concentrations under 10 mg N•L -1 (Figure 4a). It has previously been reported that microalgae activity is significantly reduced at nitrogen concentrations below 10 mg N•L -1 (Pachés et al, 2018). Under these conditions, the microalgae growth rate in the non-nitrification-inhibited PBR was therefore reduced because of limiting nitrogen, and AOB activity was favoured when the ammonium load increased after day 65, reaching negligible AOB activity was seen below 32 ºC.…”
Section: Effect Of Temperature In Microalgae-aob Bacteria Competitionmentioning
confidence: 87%
“…It must be highlighted that factors which influence microalgae growth such as solar irradiance [24;39], temperature [54,55], nutrient loading rates [8,53] and culture mixing [17,30] were the same for PBR-A and PBR-B in each experiment, only differing in the artificial lighting regime. In addition, nutrients were maintained in replete conditions (i.e., nitrogen higher than 10 mg N•L -1 and phosphorus above negligible concentration as explained in Pachés et al [62]) during all the Experiments except for 1 and 2A (Figure 2a). Hence, microalgae were only considered to be nutrient-limited in PBR-A…”
Section: Discussionmentioning
confidence: 73%